Innovating numeracy learning through geogebra-integrated modules: An Indonesian secondary school study - Ilyas, Muhammad; Ma'rufi, Ma'rufi; Basir, Fahrul; Ekawati, Shindy (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aimed to design and evaluate an instructional module integrating GeoGebra to strengthen junior secondary students’ mathematical literacy and numeracy. The module was intended to support students in interpreting, analyzing, and applying mathematical concepts in contextual and meaningful ways..Method: Adopting a modified three-phase 4D instructional design model (Define, Design, Develop), the research was implemented with eighth-grade students at SMP Negeri 3 Palopo. Data were obtained from expert validation, student feedback, classroom observations, and post-intervention tests of literacy and numeracy competencies.Findings: The validation process produced an average expert rating of 3.75, categorizing the module as highly valid. Practicality was evidenced by strong classroom implementation (96.88%), high levels of student engagement (83.17%), and positive learner responses (83.38%). Post-intervention assessments yielded an average score of 77.20, confirming that all participating students achieved at least a proficient level.Significance: The GeoGebra-enriched module represents a promising instructional innovation for mathematics education. Its integration of visual interactivity and contextual problem solving significantly enhanced students’ literacy and numeracy, underscoring its potential as a scalable model for curriculum development. Beyond its practical contributions, this study advances theoretical discourse on technology-enhanced mathematics learning by demonstrating how dynamic visualization tools can be systematically embedded into curricula. It thereby provides a critical link between digital pedagogy and the cultivation of mathematical literacy and numeracy in secondary education.